ECOLOGICAL ASSESSMENT OF THE CONDITION OF PASTURES IN THE AKTOBE REGION (ҚазҰУ хабаршысы. Экология сериясы, 2025)
Pastures are essential to agriculture, particularly in areas with harsh climates and limited nutrient availability. They serve as an effective and economically viable alternative to conventional ruminant feeding methods while enabling the simultaneous production of other agricultural goods. In Kazakhstan's Aktobe region, conducting ecological assessments of pasture lands is a key priority for agricultural producers, as these lands form the primary feed source for cattle, sheep, and horses.The main goal of this study was to scientifically evaluate the current state of pasture ecosystems and perform an ecological assessment to ensure their sustainable use. Analysis of the pasture load across the region's districts revealed clear signs of ecosystem recovery and measured the extent of anthropogenic impact on these lands. From 1991 to 2023, the decline in livestock numbers has led to a reduction in pasture load and the gradual re-establishment of ecological equilibrium.Furthermore, the study identifies the critical factors that contribute to the restoration of degraded pastures and offers comparative indicators for each district. This approach allows for a comprehensive assessment of the recovery levels of degraded pastures in the Aktobe region and helps chart out strategies for their further rational and sustainable utilization.Keywords: ecosystems, pastures, grazing load, environmental assessment, degradation, desertification